(untitled) (Journal Of Educational and Psychological Researches, 2022)
The aim of the research is to identify the educational and psychological effects of the positive and negative aspects of using social networking websites. The researcher administered a number of questions to (250) users of different types of social networking websites. He analyzed his research results and obtained a number of results. The research has reached a number of recommendations and suggestion: Regulating the use of social media. Monitoring the parents of the sites used by children in a way that they do not feel they are observers. It is necessary to devote an hour daily to show the importance of real social life for children other than using social media. It is necessary to show the importance of choosing friends who have a good reputation. It is necessary to assign a little time each week to meet family outside the house or visit relatives that help children to communicate with other changing the electronic communication to the real social media. It is necessary to show television programs to alert young people to the dangers of addiction to the psychological and educational internet. It is necessary to prepare annual calendar posters that alert students in schools and universities to the type of risks, including the risks of incorrect use of the Internet. It is necessary to prepare an educational curriculum that is not intended for the exam and does not fall within the exams and grades in the schools and universities, as much as it aims to build psychological and educational values according to the customs and traditions of ancient Iraq.